1993
DOI: 10.1002/mrm.1910290109
|View full text |Cite
|
Sign up to set email alerts
|

Localized proton MR spectroscopy of citrate in vitro and of the human prostate in vivo at 1.5 T

Abstract: Citrate is a secretory product of the normal prostate, a lack of citrate in prostate tissue is expected to be pathognomonic for adenocarcinoma. In the present study proton AB-signal characteristics of citrate at low field strength of 1.5 T were investigated by volume selective spectroscopic and theoretical methods. The nonappearance of fast phase modulation of the J-coupled system at low field strength in vivo is verified by measurements of sodium citrate solution. In vivo localized spectroscopy of small volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…Many magnetic resonance spectroscopy (MRS) studies of choline metabolism have shown increased levels of total Cho (tCho) in cancers developing in different organs, such as brain, 1-5 prostate [6][7][8] and breast. [9][10][11][12][13] The increase of tCho in tumors has become a potentially important biomarker in cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many magnetic resonance spectroscopy (MRS) studies of choline metabolism have shown increased levels of total Cho (tCho) in cancers developing in different organs, such as brain, 1-5 prostate [6][7][8] and breast. [9][10][11][12][13] The increase of tCho in tumors has become a potentially important biomarker in cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These values predict minimum water line widths of 5 Hz for kidney and about 1 0 Hz for liver or skeletal muscle. For the kidney, with respiratory triggering and localized shimming, we found that water line widths as low as 6 Hz could be achieved. …”
Section: Human Studies In Vivomentioning
confidence: 95%
“…In vivo applications using the double spin echo method are well known from literature (19)(20)(21)(22)(23)(24)(25)(26), and restriction to a few spectra should be sufficient. Figure 12 shows a 2 mL spectrum from the human calf muscle obtained with the sequence of Fig.…”
Section: In Vivo Applicationsmentioning
confidence: 99%